Pengaruh Pengetahuan dan Sosialisasi Terhadap Efektivitas Mobile Banking di Kabupaten Kepulauan Meranti - Diana, Riska (Asosiasi Dosen Akuntansi Indonesia, 2025)
Growing customer trust in a product is not easy, especially products related to financial transactions such as mobile banking.There are several factors that influence both internally and originating from within the community such as the level of knowledge, as well as external influences, namely the stimulation provided by the company by means of socialization of the product by the bank. This study aims to determine the effect of Knowledge and Socialization on the effectiveness of mobile banking in Meranti Islands District. This research is a type of descriptive quantitative research. The research results show that the influence of knowledge and socialization on the effectiveness of mobile banking in Meranti Islands Regency is 70.8%. Partially there is a positive and significant effect of Knowledge on the effectiveness of mobile banking, and socialization partially has a positive and significant effect on the effectiveness of mobile banking, besides that based on the simultaneous test (test f) there is also the effect of knowledge and socialization on the effectiveness of mobile banking in Meranti Islands Regency.